On µ-symmetries, µ-reductions, and µ-conservation laws of Gardner equation. Issue 1 (2nd January 2019) - Orhan, Özlem; Özer, Teoman
Abstract : In this study, we represent an application of the geometrical characterization of µ -prolongations of vector fields to the nonlinear partial differential Gardner equation with variable coefficients. First, µ -symmetries and the corresponding µ -symmetry classification are investigated and then µ -reduction forms of the equations are obtained. Furthermore, µ -invariant solutions are determined and µ -conservation laws of Gardner equation are studied.